National housing blueprint: social set - E.N. Rudskaya (Advanced Engineering Research, 2009)
Top-priority national blueprint "Accessible & Comfortable Houseroom for Russian Citizens" is based on a federal purposive program "Home" & channeled into the solution of social problems which need concentration of material & administrative resources of the Federal Center & regional authorities. The article is about a problem of houseroom availability for some communities and a role of the government in its solution